ANALISA TINGKAT RESAPAN TANAH BERDASARKAN PENGUKURAN PERMEABILITAS TANAH (Studi Kasus Kecamatan Tampan Kota Pekanbaru) - Usman Malik; Indra Gunawan; Juandi M (Komunikasi Fisika Indonesia, 2018)
Research was conducted to analyze the soil absorption level based on measurements of soil permeability in District Tampan Pekanbaru City, by taking soil samples for 16 units in four villages namely Simpang Baru, Delima, Tuah Karya, and Sidomulyo Barat which consists of four research blocks. Data inputted into the surfer’s software 11 to be processed so as to produce a contour map of soil absorption level. The results that highest soil absorption of the land in Tuah Karya Village of 108,090.50 m3/year whereas lowest soil absorption of the land in Simpang Baru Village of 91,149.35 m3/year. High soil absorption level caused by open spaces area was large and the amount of rainfall that absorbed into the soil and soil absorption coefficient was high. While the low soil absorption level caused by open spaces area was small and the least rainfall that absorbed into the soil and the soil absorption coefficient is low.